Glucose and Hydration Monitoring Techniques: Current Trends and Future Frontiers - Emille Triane F. Cruz; Allen A. Reyes; Carla Katrine P. Lucero; Abishai Andrei C. Sagun; Joseph Rey H.S. Agueda; Angelo Earvin Sy Choi (Chemical Engineering Transactions)
Diabetes is one of the most prevalent health diseases that is characterized by elevated blood glucose levels. It is considered a primary cause of morbidity and mortality, affecting approximately 425 million people worldwide. This paper discusses recent studies about currently available and utilized techniques for glucose and hydration monitoring. It aims to highlight the advantages and disadvantages of existing devices and methods and identify future advancements in improving processes involved in glucose and hydration monitoring. Various glucose monitoring techniques are classified as invasive, minimally invasive, and non-invasive. Proper hydration is essential for improving physical performance and lowering the risk of dehydration, which can lead to severe diabetes-related emergencies. Numerous approaches for hydration monitoring include thermal, colorimetric, and piezoresistive sensing. Due to the need for accurate and precise blood glucose control in diabetes management, biosensors are widely employed. 3D printing is primarily used to manufacture components with precise dimensions and smooth surfaces, which are crucial for developing highly sensitive sensors. These improvements are expected to offer high-accuracy results and show real-time readings, marking an opportunity for future breakthroughs in monitoring technologies.